2016
DOI: 10.1371/journal.pone.0154076
|View full text |Cite|
|
Sign up to set email alerts
|

Akap1 Deficiency Promotes Mitochondrial Aberrations and Exacerbates Cardiac Injury Following Permanent Coronary Ligation via Enhanced Mitophagy and Apoptosis

Abstract: A-kinase anchoring proteins (AKAPs) transmit signals cues from seven-transmembrane receptors to specific sub-cellular locations. Mitochondrial AKAPs encoded by the Akap1 gene have been shown to modulate mitochondrial function and reactive oxygen species (ROS) production in the heart. Under conditions of hypoxia, mitochondrial AKAP121 undergoes proteolytic degradation mediated, at least in part, by the E3 ubiquitin ligase Seven In-Absentia Homolog 2 (Siah2). In the present study we hypothesized that Akap1 might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…In the current study, our findings showed that loss of AKAP1 increased LC3-II protein expression but decreased p62 protein expression in AKAP1 −/− retina. Intriguingly, AKAP1 −/− heart reduced p62 protein expression and enhanced mitophagy and apoptosis 46 . Collectively, our results suggest that the increased LC3-II and decreased p62 contribute to the induction of autophagy/mitophagy in AKAP1 −/− retina.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the current study, our findings showed that loss of AKAP1 increased LC3-II protein expression but decreased p62 protein expression in AKAP1 −/− retina. Intriguingly, AKAP1 −/− heart reduced p62 protein expression and enhanced mitophagy and apoptosis 46 . Collectively, our results suggest that the increased LC3-II and decreased p62 contribute to the induction of autophagy/mitophagy in AKAP1 −/− retina.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that AKAP1 loss induces an imbalance of mitochondrial dynamics by triggering mitochondrial fission and loss in RGCs. AKAP1 loss promotes mitochondrial abnormalities and mitophagy in cardiac injury 46 . Based on our current findings of mitochondrial fission and loss, we determined whether AKAP1 loss induces mitophagosome formation.…”
Section: Akap1 Loss Causes Mitochondrial Fission and Mitophagosome Fomentioning
confidence: 99%
“…Single nucleotide polymorphisms in Akap1 can alter the subcellular distribution of AKAP1 variants and alter the outcomes of cAMP/PKA signaling . Indeed, the relative levels of AKAP1 on the mitochondria can influence the outcomes of local PKA signaling . By merely increasing AKAP‐1 concentrations on mitochondria, investigators have been able to leverage the prominent concentrations of PKA in the cytosol to influence mitochondrial health.…”
Section: Omm Scaffold Proteinsmentioning
confidence: 99%
“…AKAP1 loss promotes mitochondrial abnormalities and mitophagy in cardiac injury 53 . Based on our current findings of mitochondrial fission and loss, we determined whether AKAP1 loss induces mitophagosome formation using Western blot, immunohistochemistry and EM tomography analyses.…”
Section: Akap1 Loss Causes Mitochondrial Fission and Mitophagosome Fomentioning
confidence: 99%